Peningkatan Produksi dan Kualitas Daging Sapi Lokal Melalui Penggemukan Berbasis Serealia pada Taraf Energi yang Berbeda - Rudy Priyanto; Asnath Maria Fuah; Edit Lesa Aditia; Muhammad Baihaqi; Muhammad Ismail (Institut Pertanian Bogor, 2015)
Local beef cattle is still the major source of domestic beef consumption, yet their productivity and quality is relatively low. This study was aimed to investigate productivity and meat quality traits of local beef cattle through fattening using cereals based concentrate containing different energy level. Nine Ongole cattle with average initial liveweight of 254.67 ± 20.7 kg and age between I1-I2 permanent incisor teeth were used in the study. They were fattened for four months and alloted into three different energy rations; they were low (ER) 57.88% TDN, medium (ES) 63.72% TDN, and high (ET) 69.67% TDN. The three rations had simmilar protein contents, between 12.42-12.96%. Observed parameters included cattle performance (ration and nutrition dry mater intake, daily gain, and feed conversion), carcass traits (carcass weight and percentage, fat thickness, and loin eye area at the 12th rib), and meat quality traits (pH, water holding capacity, tenderness, cooking loss, marbling score, and meat color). The results showed that cattle fed with high energy (ET) ration had the highest body weight and marbling score, and more efficient in feed conversion than medium (ES) and low energy (ER) rations. Local beef cattle productivity and there meat quality could be improve through fattening using high energy cereals based concentrate.